2013
DOI: 10.22463/0122820x.443
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación de la motilidad espermática a través del sistema C.A.S.A de semen caprino criopreservado bajo diferentes medios diluyentes

Abstract: El estudio evaluó la motilidad espermática y su efecto postdescongelación en semen caprino, en dos medios comerciales (Andromed® y TwoStep®) y diferentes protocolos de congelación (medio completo, con adicción del 10% de yema de huevo, semen centrifugado y sobrenadante seminal), se utilizaron machos de la raza alpina de la Universidad Francisco de Paula Santander Ocaña, el semen fue colectado con electroeyaculador, una vez los medios terminados y parte de los contenidos seminales enteros o centrifugados mezcla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…Likewise, it is a useful tool in conducting researches where evaluating the semen is necessary or for treatments such as those developed in this study. However, although this study only considered the mass and progressive motility variables, all the sperm cell variables that the CASA system includes must be taken into consideration, including curvilinear velocity, progressive velocity, linear velocity, linearity index, straightness index, oscillation index, and mean amplitude of lateral head displacement (Hernández-Corredor et al, 2013). These variables provide objective parameters for the evaluation of semen diluted in different extenders to facilitate the standardization of the morphometric characteristics of spermatozoa (Vicente-Fiel et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, it is a useful tool in conducting researches where evaluating the semen is necessary or for treatments such as those developed in this study. However, although this study only considered the mass and progressive motility variables, all the sperm cell variables that the CASA system includes must be taken into consideration, including curvilinear velocity, progressive velocity, linear velocity, linearity index, straightness index, oscillation index, and mean amplitude of lateral head displacement (Hernández-Corredor et al, 2013). These variables provide objective parameters for the evaluation of semen diluted in different extenders to facilitate the standardization of the morphometric characteristics of spermatozoa (Vicente-Fiel et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Diaz et al (2015) also evaluated sperm quality over time (0, 2, 4, 6, and 24 h) with different extenders and found that the best MM is recorded 4 to 24 h after the semen has been refrigerated at 5 °C. Because there is scarce information about the parametric evaluation of buck sperm using the CASA system (Hernández-Corredor et al, 2013), it would be advisable to highlight that this system represents an innovative technology that determines the values of the behavior of spermatozoa stored under fresh, refrigerated, or frozen conditions (Quintero-Moreno et al, 2011). Coupled with an adequate selection of an extender for the conservation of buck semen (Hernández-Corredor et al, 2013), this system is a practical alternative for the conservation of the germplasm that is used in species improvement programs.…”
Section: Resultsmentioning
confidence: 99%
“…Table 3 shows the results of the descriptive statistics for the motility parameters evaluated using the CASA system. A straightness index (STR) of 68.75% was identified, considered as a slow movement for this parameter according to Hernández et al (2013). Masenya et al (2011) in a comparative study on semen characteristics in Kolbroek (South African indigenous breed) and Large White pigs using the CASA system, obtained the following results for each breed, respectively: VCL (143.3μm/s and 129.1μm/s), VSL (40.9 μm/s and 32.8μm/s), VAP (90.6μm/s and 81.1μm/s), LIN (29.2% and 25.7%), STR (45.8% and 41.2%) and WOB (64.4% and 62.6%), being the VCL and the VAP higher than those obtained in the present work.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, some authors indicated that an increase in the viscosity of the extender due to the presence of larger molecules in its composition induces this type of curvilinear movement, which occurs naturally in cervical mucus [54]. The viscosity of cervical and oviductal mucus induced hyperactivation of spermatozoa [55,56], and the viscosity of the extender can similarly influence sperm motility [57,58]. This hyperactivity led to a change in motility, increasing VCL and ALH values and decreasing VSL [43,55].…”
Section: Discussionmentioning
confidence: 99%